The influence of capital system categories on Human Development Index in Brazil. (2015) - Fachinelli, Ana Cristina; Giacomello, Cíntia Paese; Larentis, Fabiano
With the capital system taxonomy adapted to Brazilian indicators as was done in previous studies, this research aims to examine the correlation among the capital system categories and how each one impacts on Human Development Index (HDI) in Brazil. The capital system is a value-based tool for knowledge cities that systematically attempts to identify and develop all their capital assets. HDI and capital system indicators from 150 Brazilian cities were listed. Statistical techniques were used for data analysis. The capital system indicators were correlated and multivariate linear regression was used to identify indicator loadings in HDI formation. With the regression model, the predicted HDI could be estimated for each municipality. The results indicate which of those capitals categories have the highest impact on the HDI and also confirms the influence of determined capitals categories over others.